2018
DOI: 10.1111/jjns.12231
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and difficulties of parents of children with a cleft lip and palate

Abstract: It is important that healthcare providers understand the difference between the fathers' and mothers' worries about their child with a cleft lip and palate. Specific support services should be offered to fathers with a high level of resilience, in terms of the acceptance of reality and problem-solving, which could increase their parenting ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(13 reference statements)
2
3
0
Order By: Relevance
“…This phenomenon resulted from the fact that mothers usually took more responsibilities on child caring in families in China, in comparison with fathers. What's more, more fathers were employed than mothers in this study, similar to other research ( 12 , 61 ). Besides, mothers had higher levels of parental involvement behaviors than fathers ( 62 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This phenomenon resulted from the fact that mothers usually took more responsibilities on child caring in families in China, in comparison with fathers. What's more, more fathers were employed than mothers in this study, similar to other research ( 12 , 61 ). Besides, mothers had higher levels of parental involvement behaviors than fathers ( 62 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we also found that perceived social support made a positive contribution to the resilience of mothers of patients with CL/P. The positive effect of social support has been confirmed in many studies, both studies on the resilience of caregivers with chronic diseases ( 35 , 69 ) and studies on psychological conditions of caregivers of patients with CL/P ( 12 , 67 , 70 ). Perceived social support is a part of the positive psychological capital of almost all patients and caregivers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…CLP is a complex malformation that involves several psychosocial factors, which can generate anxiety, insecurity, and even guilt or rejection by the patient's family (UEKI et al, 2019). In addition, the family's daily life requires some adaptations, due to the treatment that usually occurs in specialized centers that are located far from their homes.…”
Section: Psychologymentioning
confidence: 99%
“…Previous studies have reported resilience among parents of children with medical conditions such as cancer, acute lymphoblastic leukemia, and type 1 diabetes (T1D; Eilertsen et al, 2015;Rosenberg et al, 2013;Yi-Frazier et al, 2017). Ueki et al (2018) explored the differences in emotional difficulties and resilience between fathers and mothers of a child with a cleft lip and palate. However, researchers only analyzed the data of 64 couples, and the sample was relatively small for a survey.…”
Section: Resilience Parents and Orofacial Cleftsmentioning
confidence: 99%